An abundance of Epsilonproteobacteria revealed in the gut microbiome of the laboratory cultured sea urchin, Lytechinus variegatus - Hakim, Joseph A.; Koo, Hyunmin; Dennis, Lacey N.; Kumar, Ranjit; Ptacek, Travis; Morrow, Casey D.; Lefkowitz, Elliot J.; Powell, Mickie L.; Bej, Asim K.; Watts, Stephen A. (Frontiers in Microbiology, 2015)
In this study, we have examined the bacterial community composition in the laboratory cultured sea urchin Lytechinus variegatus gut microbiome and its culture environment using NextGen amplicon sequencing of the V4 segment of the 16S rRNA gene, and downstream bioinformatics tools. Overall, the gut and tank water was dominated by Proteobacteria, whereas the feed consisted of a co-occurrence of Proteobacteria and Firmicutes at a high abundance. The gut tissue represented Epsilonproteobacteria as dominant, with order Campylobacterales at the highest relative abundance (>95%). However, the pharynx tissue was dominated by class Alphaproteobacteria. The gut digesta and egested fecal pellets had a high abundance of class Gammaproteobacteria, from which Vibrio was found to be the primary genus, and Epsilonproteobacteria, with genus Arcobacter occurring at a moderate level. At the class level, the tank water was dominated by Gammaproteobacteria, and the feed by Alphaproteobacteria. Multi-Dimensional Scaling analysis showed that the microbial community of the gut tissue clustered together, as did the pharynx tissue to the feed. The gut digesta and egested fecal pellets showed a similar relationship to the tank water. Further analysis of Campylobacterales at a lower taxonomic level using the oligotyping method revealed 37 unique types across the ten samples, where Oligotype 1 was primarily represented in the gut tissue. BLAST analysis identified Oligotype 1 to be Arcobacter sp., Sulfuricurvum sp., and Arcobacter bivalviorum at an identity level >90%. This study showed that although distinct microbial communities were evident across multiple components of the sea urchin gut ecosystem, there is a noticeable correlation between the overall microbial communities of the gut with the sea urchin L. variegatus culture environment.